Psychophysical and cognitive adverse effects of smart phones overuse on children and adolescent - Noorjan Abdullah Muhammed; Mufeed Akram Taha (Medical Journal of Babylon)
Abstract Background: The excessive use of smartphones is seen as a source of child and adolescent violence and probably impacts cognitive function. As the world of mobile phones are continuously evolving, the violence factor is an endless argument. Smart mobile can cause problems other than violence which might be physical, cognitive, or psychological. Objectives: The study aims to clarify the dangers of smartphones overuse on psychophysical and cognitive function. Materials and Methods: A prospective follow-up study was conducted that included 100 children. A convenient sample of participants and their parents were interviewed directly and were asked about their children’s smart phones habit, causes of cellular phone overuse, school performance. Participants behavior was assessed by Modified overt aggression scale, whereas cognitive function by Montreal Cognitive Assessment test was done in 1, 6, and 12 months interval. Results: 50% of participants used smartphones for more than 3 hours per day, as well as most of the cases who used smartphones for a longer duration were children (25%) as compared to other age groups, children used smartphones mainly for violent and nonviolent games than in social applications, excessive mobile phone usage for more than 3 hours daily associated with significant health problems like neck pain (68%), headache (52.1%), eye tearing (51%), sleep problems (47.6%), and backache (47.1%). Children and adolescents who used smartphones for less than 1 hour daily show an increment in their scores, whereas those who used smartphones for more than 1 hour daily gradually decreased their scores with the time used. Conclusion: Smartphone overuse had a significant impact on behavior, school performance, and cognitive function.